Contagious Protests - Arezki, Rabah; Dama, Alou Adesse; Djankov, Simeon; Nguyen, Ha (World Bank, Washington, DC, 2020)
This paper explores the spillover of protests across countries using data on nonviolent and spontaneous demonstrations for 200 countries from 2000 to 2020. Using an autoregressive spatial model, the analysis finds strong evidence of "contagious protests," with a catalyzing role of social media. In particular, social media penetration in the source and destination of protests leads to protest spillovers between countries. There is evidence of parallel learning between streets of nations alongside the already documented learning between governments.